2019
DOI: 10.12669/pjms.35.1.365
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors for deep venous thrombosis in patients with gynecological malignant tumor: A clinical study

Abstract: Objectives: To determine the clinical characteristics and risk factors of Deep Venous Thrombosis (DVT) in patients with gynecological malignant tumor, facilitating gynecologists better prevent the fatal complication. Methods: The patients with gynecological malignant tumor treated in department of gynecology of our hospital between May 2013 and May 2018 were reviewed retrospectively. The clinical data of patients including gender, age, tumor staging, adenocarcinoma, surgery, operation time, hypertension,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Regarding malignancy, patients who received gynecologic cancer surgery were considered to be at high risk of DVT due to advanced age, cancer type, presence of pro-thrombotic mutations, pelvic mass compressing the major pelvic veins, endothelial cell injury during pelvic lymphadenectomy, lengthy surgical procedures, and thrombogenic chemotherapy [ 17 , 18 ]. In the present study, five from six patients were diagnosed with a malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding malignancy, patients who received gynecologic cancer surgery were considered to be at high risk of DVT due to advanced age, cancer type, presence of pro-thrombotic mutations, pelvic mass compressing the major pelvic veins, endothelial cell injury during pelvic lymphadenectomy, lengthy surgical procedures, and thrombogenic chemotherapy [ 17 , 18 ]. In the present study, five from six patients were diagnosed with a malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…However, in certain populations, hypertension showed a strong influence on DVT. Li Qun et al [ 21 ] explored the risk factors of DVT in patients with gynecological malignancies and found that hypertension was one of the independent influencing factors (OR = 2.638, 95% CI: 1.523–4.539, P < 0.0001). A meta-analysis conducted by Ageno et al [ 22 ] found that the VTE risk was increased in patients with classic cardiovascular disease risk factors, including obesity (OR = 2.3), high blood pressure (OR = 1.5), diabetes (OR = 1.4), and hyperlipidemia (OR = 1.2).…”
Section: Discussionmentioning
confidence: 99%
“…Radiochemotherapy is a common treatment for gynecological tumors. It has been reported that radiotherapy is an independent risk factor for thrombosis in patients with tumor [ 21 ]. Recording radiotherapy-related information and analyzing the risk of thrombosis can help prevent thrombosis and improve the quality of life of patients receiving radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that DVT is a complex multifactorial disease influenced by several risk factors, including surgery and trauma, prolonged immobilization, myeloproliferative disorders, pregnancy and postpartum status, weight, age, smoking status and corticosteroid treatment. [15][16][17] In addition, radiotherapy and cancer increase the risk of developing DVT, [18][19][20] and the reported cumulative incidence of venous thrombosis in cancer patients is 1-8%. 21 Moreover, after radiotherapy, changes in the structure of the pelvic tissue, the blood composition and the vessel wall are more rapid than those of fibrosis, 22,23 and radionecrosis and granulation of the small lymphatic vessels, lymph nodes, and soft tissue around vessels following radiotherapy can lead to the accumulation of protein-rich fluid in soft tissues secondary to inadequate lymphatic drainage.…”
Section: Introductionmentioning
confidence: 99%